2017
DOI: 10.1371/journal.pone.0171056
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Catalytic Mechanism of CouO, a Versatile C-Methyltransferase from Streptomyces rishiriensis

Abstract: Friedel–Crafts alkylation of aromatic systems is a classic reaction in organic chemistry, for which regiospecific mono-alkylation, however, is generally difficult to achieve. In nature, methyltransferases catalyze the addition of methyl groups to a wide range of biomolecules thereby modulating the physico-chemical properties of these compounds. Specifically, S-adenosyl-L-methionine dependent C-methyltransferases possess a high potential to serve as biocatalysts in environmentally benign organic syntheses. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…Most importantly, however, C-methylation had to occur strictly before ortho O-glucosylation. In agreement with recent mechanistic proposals, [40][41][42] 7-O-β-D-glucosylation precluded subsequent C-methylation at the adjacent position 8, probably by preventing acceptor activation through deprotonation of 7-OH. Therefore ortho C-methylation and O-glucosylation have to be performed sequentially, independent of the acceptor and the pair of enzymes used.…”
Section: Discussionsupporting
confidence: 90%
“…Most importantly, however, C-methylation had to occur strictly before ortho O-glucosylation. In agreement with recent mechanistic proposals, [40][41][42] 7-O-β-D-glucosylation precluded subsequent C-methylation at the adjacent position 8, probably by preventing acceptor activation through deprotonation of 7-OH. Therefore ortho C-methylation and O-glucosylation have to be performed sequentially, independent of the acceptor and the pair of enzymes used.…”
Section: Discussionsupporting
confidence: 90%
“…One C‐MT exemplar is NovO, which methylates the C‐8 position of 1 a in the biosynthesis of the antibiotic novobiocin to form 2 a (Scheme A) . We and others have shown that regiospecific methylation of the 8‐position of 1 b is catalysed by a novel His‐Arg motif, which facilitates the deprotonation of the phenolic proton in the 7‐position, followed by methylation at position 8 by SAM to form 2 b . NovO is also effective in catalysing Friedel–Crafts alkylations by using non‐natural SAM analogues to alkylate 1 b – d regiospecifically .…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] However,o btaining regiospecificity,p articularly when this is required at alate-stage in asynthetic workflow,is an enduring challenge. [14][15][16][17] Ther epertoire of C-methylation extends to small molecules,which opens up opportunities to tailor these enzymes as ag eneral platform for biocatalytic C À Cb ond formation (Figure 1a). [14][15][16][17] Ther epertoire of C-methylation extends to small molecules,which opens up opportunities to tailor these enzymes as ag eneral platform for biocatalytic C À Cb ond formation (Figure 1a).…”
mentioning
confidence: 99%
“…[27,28] Am ore step-and atom-efficient strategy is to couple cofactor formation with C-alkyl transfer. [15,27,29,35,36] Although in-depth knowledge of the substrate promiscuity of C-MTases has been garnered from structural and mutagenesis studies, [17,19,20,37] little is known about how the structural features of the SAM cofactor itself influences the yield and scope of C-alkylation. [34] ClDAi sashelf-stable,a tom-economical adenosine source for such aprocess catalyzed by SalL compared to ATP, which is asubstrate for SAM production by methionine adenosyltransferase (MAT).…”
mentioning
confidence: 99%
See 1 more Smart Citation